Increase of infectious syphilis among heterosexuals in Amsterdam: its relationship to drug use and prostitution. - van den Hoek, J A (1990)
Since 1986, an increase in heterosexually acquired syphilis cases has been seen in Amsterdam. The proportion of syphilis patients who reported using hard drugs, increased from 7% in 1985 to 23% in 1988, which was mainly due to increased numbers of addicted prostitute women with syphilis.